If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = -6x + -30 Reorder the terms: 9x = -30 + -6x Solving 9x = -30 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9x + 6x = -30 + -6x + 6x Combine like terms: 9x + 6x = 15x 15x = -30 + -6x + 6x Combine like terms: -6x + 6x = 0 15x = -30 + 0 15x = -30 Divide each side by '15'. x = -2 Simplifying x = -2
| 4y+16=3.3y-1.3 | | s^2+9s=-20 | | x/5-9=9 | | 75a^3+90a^2+27a=0 | | w/3+18=21 | | 38.5=9/5(F-32) | | 5x=9x-15 | | k+23.7=23.7 | | 30x^2+5x-10=0 | | y=4x-4 | | F=9/5(38.5-32) | | X^2+10x+25=36 | | 2r^2+392=56r | | 6n-1=5n-7 | | 8x+24=12x | | 38.5=5/9(F-32) | | x^4-3x^2-8x^3=0 | | 6y=4y^2 | | 16x+280=8x^2 | | -6z-(2x+8)+10z= | | 12x^2-3x-1=0 | | 900x^2=625 | | 5x^2-9x-18=0 | | 41-8x-9=-6x-9-23 | | 1*9= | | ln(x-7)-ln(x+2)=ln(x-4)-ln(x+2) | | s-(-4s+2)=13 | | 10-4(l+7)=2(1-L) | | 2[3+2x+9]=28x+132 | | x^2+4x=15 | | l=10-2w | | 2x^2-7x+25=0 |